Business intelligence success factors : tools for aligning your business in the global economy - Rud, Olivia Parr (Joh Wiley & Sons, 2009)
Why BI-intensive companies fail to thrive during economic volatility and how they can become more adaptable and resilient. Written by an expert in data mining and business intelligence, this timely book discusses the latest practices emerging in organizational development that support business intelligence-intensive companies. Thoroughly exploring components of quantum physics, chaos theory, complexity science, and evolutionary biology to provide a scientific framework for a new corporate model, Business Intelligence Success Factors explains why these practices and competencies are critical gi.- Resumé vydavatel
Keywords: business intelligence; globalizace; globalization; elektronické knihy; sborníky; electronic books; papers of several authors